2015
DOI: 10.1039/c5dt03398e
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical preparation of nanocrystalline biocompatible single-phase Mn-doped A-type carbonated hydroxyapatite (A-cHAp): effect of Mn doping on microstructure

Abstract: Nanocrystalline biocompatible single-phase Mn-doped A-type carbonated hydroxyapatite (A-cHAp) powder has been synthesized by mechanical alloying of a stoichiometric mixture of CaCO3, CaHPO4·2H2O and MnO powder for 10 h at room temperature under open air. The A-type carbonation in HAp (substitution of CO3(2-) for OH(-)) is confirmed by FTIR analysis. Microstructure characterization in terms of lattice imperfections and phase quantification of ball milled samples are made by analyzing XRD patterns employing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 48 publications
0
7
0
1
Order By: Relevance
“…In general, the EPR spectra of Mn 2+ -containing compounds are sufficiently complex, especially in low-symmetry polycrystalline systems, as the averaging across all possible single crystal orientations and the overlap of signals from multiple possible sites lead to the broadening of the spectra. The obtained spectra showed typical Mn 2+ EPR spectral featureszero field splitting of the 6 S 5/2 ground state and hyperfine (HF) coupling to the 100% abundant 55 Mn nuclear spin I = 5/2. 40,49 No resonance signals were observed in the undoped sample.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In general, the EPR spectra of Mn 2+ -containing compounds are sufficiently complex, especially in low-symmetry polycrystalline systems, as the averaging across all possible single crystal orientations and the overlap of signals from multiple possible sites lead to the broadening of the spectra. The obtained spectra showed typical Mn 2+ EPR spectral featureszero field splitting of the 6 S 5/2 ground state and hyperfine (HF) coupling to the 100% abundant 55 Mn nuclear spin I = 5/2. 40,49 No resonance signals were observed in the undoped sample.…”
Section: Resultsmentioning
confidence: 95%
“…Figure schematically shows the β-TCP structure accommodating Mn 2+ ions. Unlike in HA, where Ca 2+ ions occupy one of two possible sites, columnar (Ca(1)) and hexagonal (Ca(2)), there are up to five different Ca 2+ positions in the TCP structure and it is widely assumed that Mn 2+ favors the substitution at the Ca(5) site, with a geometry close to that of a regular octahedron. , In contrast, both Ca(1) and Ca(2) positions in the HA structure are filled by Mn 2+ even at very low concentrations of manganese, with the caveat that calcium vacancies are expected to be the first to be populated by Mn 2+ ions . However, as for HA, there is no reason not to assume that Mn 2+ could substitute Ca 2+ ions other than those residing in the Ca(5) position of the TCP structure (Figure ), such as, for example, Ca(4) and Ca(3) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The splitting peaks at 1,400 and 1,460 cm −1 suggested that carbon from the organics entered into the hydroxyapatite crystal (Fathi, Hanifi, & Mortazavi, ). Carbonate usually exists in hydroxyapatite of natural fish bones in the form of type‐B carbonate substitute (PO43- was substituted by CO32-) (Ivanova, Frank‐Kamenetskaya, Kol'tsov, & Ugolkov, ), which accounts for 2%–4% of mineral mass (Lala, Ghosh, Das, Kar, & Pradhan, ). Therefore, the disappeared peaks at around 1,452 cm −1 indicated the CO32- groups escaped from hydroxyapatite.…”
Section: Resultsmentioning
confidence: 99%
“…Ca1 and Ca2 are crystallographically inequivalent sites in HAp, and both have the potential for substitution of foreign ions. Although the preferred Ca site for different foreign ions is still under debate, more studies have suggested that Ca2 is the preferred site based on Rietveld analysis of XRD data and first principles calculations (Guerra-López et al, 2015;Lala et al, 2015;Luo et al, 2009;Terra et al, 2010). In this study, the local environment of Ca and Cd in This is the peer-reviewed, final accepted version for American Mineralogist, published by the Mineralogical Society of America.…”
Section: Site Preference Of CD Incorporation Into Hapmentioning
confidence: 74%